Innovations in corporate governance : global perspectives - Watson, Susan, 1963-; Vasudev, P. M.; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
The world is changing. After old certainties were swept away by the Financial Crisis of 2008-09, states are grappling with the implications of new thinking about the role and nature of corporations and how they should be regulated. This timely book brings together the contributions of leading scholars from around the world to highlight and provide critical analysis of developments and trends in corporate governance in a range of jurisdictions, both mature and developing. The diverse subjects covered in the book include shareholder protection in Delaware, trends in the governance of state-owned enterprises in China, say on pay in the Netherlands, board committees in the UK, and stakeholder governance in Germany. The book also includes theoretical perspectives, including one chapter arguing against the notions of shareholder primacy that underpin Anglo-American corporate law. The final section presents two chapters on the governance of banks, reflecting the contemporary importance of financial institutions. Innovations in Corporate Governance offers an essential global perspective on corporate governance that will be of interest to students and academics in the field, as well as professionals, policy makers and those working in regulatory agencies around the world.
1. Introduction / Susan Watson and P.M. Vasudev -- 2. Globalizing up corporate law / Franklin A. Gevurtz -- 3. China's national champions: governance change through globalization? / Li-Wen Lin -- 4. The taxonomy of the modern company / Susan Watson -- 5. Corporate governance codes as regulatory tools to advance stakeholder concerns in the corporation / Brigitte Haar -- 6. Empire-building: the rise of the audit committee / Brenda Hannigan -- 7. Answering the say for no pay / Christoph Van der Elst -- 8. Banks, corporate governance and the public interest: the potential role of public interest directors / Gail E. Henderson -- 9. Organisational form and financial stability: lessons from cooperative banks in the US and UK / Michael Marin -- Index.
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: řízení a správa společností; corporate governance; e-knihy online; e-books online